A Call to Action for Leveraging Cultural Capital and Funds of Knowledge in Academic Integration of South Asian International Students in STEM Programs at Canadian Universities - Chowdhury Rahul, Shuvo (Peer Beyond Graduate Research Conference, 2025)
The Internationalization of post-secondary STEM education enriches global knowledge exchange yet causes cultural, linguistic, and psychological challenges for South Asian international students. This discussion underscores the importance of implementing academic initiatives that recognize diverse cultural backgrounds and funds of knowledge. Incorporating asset-based strategies fosters inclusive participation, a sense of belonging, and better academic integration. Collaborative and systemic approaches can transform Canadian STEM programs into more equitable, innovative and engaging learning communities.